Motherhood through medically assisted reproduction – characteristics and motivations of Swedish single mothers by choice. (27th May 2021) - Volgsten, Helena; Schmidt, Lone
Abstract: Characteristics and motivations of single mothers by choice were assessed in this pilot study, after new legislation in 2016 allowing access to medically assisted reproduction (MAR). Single women at a university clinic in Sweden were sent a postal questionnaire to their home address ( n  = 86) and 54 (62.8%) women filled it out and returned it. The women had a mean age of 35.1 years and were well-educated. Most of them worked full-time, were permanently employed, and had a stable income. They had previously had long-term relationships, although these had not been right for having children. More women (61%) could consider embryo donation rather than adoption (50%) ( p  < 0.05). The motivations most commonly cited for choosing motherhood by MAR was that because of their age, having a child was more important than waiting for the right partner. Nevertheless, they still had hope to find a partner in the future. In conclusion, Swedish single women accepted for MAR are no different from other single mothers by choice: they are financially and socially stable, and choose motherhood by MAR due to their advanced age and not wanting to wait too long in order to meet the right partner.